Analisis Pembangunan Sistem Informasi Pengelolaan Lingkungan Bebas Sampah Terintegrasi di Wilayah Pariwisata Indonesia - Leonardi Paris Hasugian; Sintya Sukarta; Raden Fenny Syafariani (ULTIMA InfoSys, 2017)
Cleanliness is one of many other indicator that have to be held by a tourism destination. It mean that the tourism destination should be clean from garbage or any other dirty things. Indonesia is a tourism destination that have been known as a beautiful and humble country to be visited. As a tourism country, Indonesia should also give a big concern to the cleanliness issue. Various criticisms and suggestions always delivered to the manager or government of the tourist sites, but the response from them was null. There have to be a research to find out what is the root of the environment cleanliness problem and which part of the improvement that was missed. This study covers how to integrate all the stakeholder by using Information Technology in order to address the environment cleanliness issue. Existing policy established will be the basis for analyzing, designing, implementing, and evaluating a product in addressing the issues of garbage. The research is developed under the PEST and SWOT method, and using the Knowledge Management System. Visual Communication Media is a product that was built to help people in controlling the outstanding garbage. Information technology is built to become a medium in managing information related to garbage problems. Meanwhile, Counseling and Socializing is held to provide learning of the importance in maintaining hygiene. The integration of these things is monitored and evaluated to obtain a comprehensive improvement. Index Terms—Cleanliness, Information Technology, Knowledge Management System.